Displacing Whiteness Essays in Social and Cultural Criticism - Angie, Chabram-Dernersesian; Bell, Hooks; Chela, Sandoval; David, Wellman; France, Winddance Twine; Frankenberg, Ruth; John, Hartigan; Phil, Cohen; Rebecca, Aanerud; Ruth, Frankenberg; T., Muraleedharan; Vron, Ware (Duke University Press, 1997)
Displacing Whiteness makes a unique contribution to the study of race dominance. Its theoretical innovations in the analysis of whiteness are integrated with careful, substantive explorations of whiteness on an international, multiracial, cross-class, and gendered terrain. Contributors localize whiteness, as well as explore its sociological, anthropological, literary, and political dimensions.Approaching whiteness as a plural rather than singular concept, the essays describe, for instance, African American, Chicana/o, European American, and British experiences of whiteness. The contributors offer critical readings of theory, literature, film and popular culture; ethnographic analyses; explorations of identity formation; and examinations of racism and political process. Essays examine the alarming epidemic of angry white men on both sides of the Atlantic; far-right electoral politics in the UK; underclass white people in Detroit; whiteness in "brownface" in the film Gandhi; the engendering of whiteness in Chicana/o movement discourses; "whiteface" literature; Roland Barthes as a critic of white consciousness; whiteness in the black imagination; the inclusion and exclusion of suburban "brown-skinned white girls"; and the slippery relationships between culture, race, and nation in the history of whiteness. Displacing Whiteness breaks new ground by specifying how whiteness is lived, engaged, appropriated, and theorized in a range of geographical locations and historical moments, representing a necessary advance in analytical thinking surrounding the burgeoning study of race and culture.Contributors. Rebecca Aanerud, Angie Chabram-Dernersesian, Phil Cohen, Ruth Frankenberg, John Hartigan Jr., bell hooks, T. Muraleedharan, Chéla Sandoval, France Winddance Twine, Vron Ware, David Wellman